PENGARUH TOKO MODERN TERHADAP MINAT KONSUMEN DAN PENDAPATAN UMKM DI DESA JATI KECAMATAN KAO - SIntia Mandoru; Faisal Y Habsyi; Anhar Drakel (Jurnal Pendidikan dan Ekonomi (JUPEK), 2023)
This research is quantitative. Data collection techniques included observation, questionnaires, and in-depth interviews. The results indicate that MSMEs' perceptions of modern stores have both positive and negative impacts. The negative impact is a decrease in MSME revenue. The positive impact is that the presence of modern stores motivates MSMEs to improve and evaluate themselves.